2021
DOI: 10.1093/conphys/coab069
|View full text |Cite
|
Sign up to set email alerts
|

The lampricide 3-trifluoromethyl-4-nitrophenol causes temporary metabolic disturbances in juvenile lake sturgeon (Acipenser fulvescens): implications for sea lamprey control and fish conservation

Abstract: The pesticide 3-trifluoromethyl-4-nitrophenol (TFM) is applied to rivers and streams draining into the Laurentian Great Lakes to control populations of invasive sea lamprey (Petromyzon marinus), which are ongoing threats to fisheries during the lamprey’s hematophagous, parasitic juvenile life stage. While TFM targets larval sea lamprey during treatments, threatened populations of juvenile lake sturgeon (Acipenser fulvescens), particularly young-of-the-year (<100 mm in length), may be adversely affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…The EC 50 values of TFM and the TFM–niclosamide mixture were 40-fold and 60-fold greater than that of niclosamide alone at all three temperatures (Table ). These EC 50 values are reflective of whole-animal acute toxicity studies, where the concentrations of TFM known to cause mortality in the sea lamprey and nontarget fishes (e.g., 9–96 h LC 50 or LC 99.9 values) are typically 10 to 50 times greater than that of niclosamide. ,− The broad agreement in sensitivity to lampricides at both the mitochondrial (RCR) and whole animal (mortality) levels strongly support our conclusion that the greater potency of niclosamide compared to TFM is primarily due to events occurring at the level of the mitochondria.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…The EC 50 values of TFM and the TFM–niclosamide mixture were 40-fold and 60-fold greater than that of niclosamide alone at all three temperatures (Table ). These EC 50 values are reflective of whole-animal acute toxicity studies, where the concentrations of TFM known to cause mortality in the sea lamprey and nontarget fishes (e.g., 9–96 h LC 50 or LC 99.9 values) are typically 10 to 50 times greater than that of niclosamide. ,− The broad agreement in sensitivity to lampricides at both the mitochondrial (RCR) and whole animal (mortality) levels strongly support our conclusion that the greater potency of niclosamide compared to TFM is primarily due to events occurring at the level of the mitochondria.…”
Section: Resultssupporting
confidence: 75%
“…At the level of the whole animal, TFM impairs the aerobic metabolism and correspondingly forces a greater reliance on anaerobic ATP production pathways such as glycolysis and high-energy phosphagens. ,,, For animals that survive exposure to lampricides, the temporary draining of the ATP pool may nevertheless lead to adverse outcomes such as decreased growth . Recent studies have shown that niclosamide has similar effects in the sea lamprey, rainbow trout, and lake sturgeon (Acipenser fulvescens), including depletion of glycogen and phosphocreatine reserves, increased lactate, and pronounced reductions in muscle intracellular pH. , Taken together, niclosamide appears to have a very similar mode of action in fishes and sea lamprey to that of TFM, but the effects of niclosamide result from concentrations that are less than 2% of those of TFM. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations